The Food Safety of Livestock Products (Meatball, Corned Beef, Beef Burger and Sausage) Studied from Heavy Metal Residues Contamination - Harlia, E; Balia, RL (ANIMAL PRODUCTION, 2010)
The aims of animal husbandry improvements are to increase both the quality and the quantity of livestock production and to ensure the safety of the product. It is necessarry for Â consumersÂ  to pay attention to the food safety of livestock product because it is related to humans health.Â  The research was conducted to determine the food safety of livestock product condition by detecting heavy metal residues on several food products from livestock like meatball, corned beef, burgerâs beef, and sausages. ThisÂ  researchÂ  was explored by using surveys method and purposive technique sampling, then the resulted data were descriptively analyzed. The observed variables were heavy metal contents such as Plumbum (Pb) and Cadmium (Cd) in which being measured by usingÂ AAS (Atomic Absorption Spectrophotometri ). The result showed that in general, heavy metal residue of Pb from several livestock products (meatball, corned beef, beef burger, and sausages) were smaller than Maximum Residue Limit (MRL), while the Cdâs residueÂ was partly over the MRL concentration, therefore further action has to be taken as it affects the humans health. (Animal Production 12(1): 50-54 (2010)Â Key words :Â  food safety, Â MRL, heavy metal Pb, Cd.